Quit smoking: methods and outcomes for Norwegian adults - Ingeborg Lund; Marianne Lund (Springer, 2023)
Abstract Background Tobacco smoking still represents one of the most significant preventable causes of death and poor health, and higher success rates for people trying to quit smoking would benefit both public and individual health. Achieving this requires better knowledge of factors that might improve the chances of successful quitting. This study aims to investigate cessation activities and explore associations between outcomes of smoking cessation attempts and use of cessation aids, previous cessation attempts, and attempt-planning. Methods Using data from a national web panel (N = 1424), smoking cessation activities and use of smoking cessation aids by people who smoke or have smoked are studied bivariately and in adjusted models. Results Almost half the sample had not used a cessation aid in the last quit attempt. Snus was the most common cessation aid, followed by NRTs and ECs. In adjusted models, snus use increased the likelihood of quitting. Planning an attempt and earlier quit attempts were associated with less quitting. Conclusion Presently, switching to snus seems to be the most effective and efficacious method for quitting smoking in Norway.